2019
DOI: 10.1021/acs.iecr.9b01921
|View full text |Cite
|
Sign up to set email alerts
|

Permanganate-Induced Efficient Mineralization of Poly(vinylidene fluoride) and Vinylidene-Fluoride Based Copolymers in Low-Temperature Subcritical Water

Abstract: Reactions of poly(vinylidene fluoride)[PVDF], poly(vinylidene fluoride-co-hexafluoropropylene) [poly(VDF-co-HFP)] copolymer, and poly(vinylidene fluoride-co-perfluoromethyl vinyl ether) [poly(VDF-co-PMVE)] copolymer in subcritical water were performed with the aim to develop a technique for recycling fluorine element. By addition of KMnO 4 to the system, quasi-complete mineralization of PVDF was achieved at a rather low temperature (250 °C). When PVDF was reacted for 18 h in the presence of KMnO 4 (158 mM, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…The patterns did not display any diffraction peaks originating from KMnO 4 , while peaks assigned to MnO 2 only were detected. This result is unsurprising because reports on the decomposition of persistent chemicals by treatment with KMnO 4 in superheated water [35][36][37] have indicated that KMnO 4 is converted to MnO 2 (Eq. 4), which then acts as the oxidizing agent.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns did not display any diffraction peaks originating from KMnO 4 , while peaks assigned to MnO 2 only were detected. This result is unsurprising because reports on the decomposition of persistent chemicals by treatment with KMnO 4 in superheated water [35][36][37] have indicated that KMnO 4 is converted to MnO 2 (Eq. 4), which then acts as the oxidizing agent.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%
“…Furthermore, KMnO 4 , a harmless oxidizing agent, is employed at tap water manufacturing facilities to treat metal compounds, preventing undesired disinfection products (e.g., trihalomethanes) [34]. So far, there have been only three reports that described KMnO 4 -induced superheated water treatment: destructions of acetic acid [35], poly(vinylidene fluoride) [-(CH 2 CF 2 ) n -] [36], and ionic liquids bearing perfluorinated anions [37].…”
mentioning
confidence: 99%
“…[7][8][9][10] However, Hori et al recently proposed an interesting technology known as mineralization, which is based on the concept of using FPs to create inorganic compounds that are comparable to minerals. To mineralize the FPs, they applied supercritical water (scH 2 O) and subcritical water (subcH 2 O) in the presence of an oxidant, [11][12][13][14] where the former is defined as water at temperatures and pressures higher than the critical point of 374 °C and 22.1 MPa, and the latter is hot water with a sufficient pressure to maintain the liquid state at temperatures ranging between 100 and 374 °C. Using this technique, both PVDF and the ethylene-tetrafluoroethylene copolymer (ETFE) were quasi-completely mineralized into F − and CO 2 in scH 2 O at 380 °C in the presence of an excess of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We report herein an effective method that allows the almost complete mineralization of two fluorinated ILs (Figure )[Me 3 PrN]­[(CF 3 SO 2 ) 2 N] and 1-methyl-1-propylpiperidium bis­(trifluoromethanesulfonyl)­imide, [C 3 mpip]­[(CF 3 SO 2 ) 2 N]in subcritical water at a relatively low temperature (300 °C) by using KMnO 4 as an oxidizing agent. In the current literature, there are only two reports of reactions performed with the combination of subcritical water and KMnO 4 : decompositions of acetic acid and poly­(vinylidene fluoride) . KMnO 4 is a safe oxidizing agent that is currently used at drinking water treatment plants to remove the iron component and to control the formation of trihalomethanes and other disinfection byproducts…”
Section: Introductionmentioning
confidence: 99%
“…In the current literature, there are only two reports of reactions performed with the combination of subcritical water and KMnO 4 : decompositions of acetic acid 45 and poly-(vinylidene fluoride). 46 KMnO 4 is a safe oxidizing agent that is currently used at drinking water treatment plants to remove the iron component and to control the formation of trihalomethanes and other disinfection byproducts. 47 As described later, in the present system, KMnO 4 is transformed into MnO 2 , which has a significant role in the mineralization of these ILs in the presence of O 2 that formed from KMnO (1) N] were purchased from Kanto Chemical (Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 99%